APPLICATION OF FUZZY MEASURES IN THE TASK OF ASSESSING THE COMPETITIVE POSITION OF THE COMPANY - Savchuk, R. V.; Skorokhodov, O. B. (Science and Transport Progress, 2007)
In this paper, is proposed an approach of enterprise competitive position estimation using fuzzy aggregation operator, on an example of enterprise that produce energy-saving technology, alternative sources of energy. A model of evaluating competitive positions of an enterprise is proposed.